OPPORTUNITIES OF SOCIO-EDUCATIONAL ASSISTANCE TO INDIVIDUALS SERVING ALTERNATIVE TO IMPRISONMENT SENTENCES: THE PROGRAMME BEHAVIOUR-CONVERSATIONCHANGE APPLICATION ANALYSIS - Žukauskienė, Lilia; Viršilas, Vaidas; Farbring, Carl Åke (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper focuses on the issue of socio-educational assistance to alcohol addicts serving non-custodial sentences in the Probation Department of Klaipėda Regional Probation Service. It comments on the results of the behavioural correction programme Behaviour-Conversation-Change (BCC), applied to the individuals serving non-custodial sentences. The research was based on the qualitative research strategy. The conducting of the research was underpinned by the works of W.R. Miller, S.Rollnick (1991, 2002) and numerous other authors on a motivational interview, as well as on a motivational interview-based programme Behaviour-Conversation-Change to be used by the penal system institutions (Farbring, Berge, 2004). The participants of the research were individuals with alcohol addicts, serving non-custodial sentences in the Probation Department of Klaipėda Regional Probation Service. In the period 2012 to 2017, 160 respondents took part in the research (accordingly, the sample was 151 respondents). The changes in the respondents' behaviour were recorded by means of the SOCRATES 8A 19 question- scale (The Stages of Change Readiness and Treatment Eagerness Scale), designed to evaluate three key components: problem recognition, ambivalence, and the steps taken (Miller, Tonigan, 1996). The changes were evaluated at the beginning and at the end of the Behaviour-Conversation-Change programme. As proved by the findings, the impact of the Behaviour-Conversation-Change programme was positive at the recognition and the step taking stages. The results achieved in the application of the Behaviour-Conversation-Change programme meaningfully differed, given the officers approach to the programme.